Measurement of the uniformity of ablation for 0.53 μm laser irradiation of spherical targets - Apte, P; Brown, D; Cole, A; Key, M; Norreys, P; Wooding, E (1988)
A novel technique of time-resolved monochromatic X-ray imaging has been used to measure the spatial variation of burn through time of an ablator layer on spherical targets irradiated by twelve laser beams of wavelength 0.53 μm and pulse duration 0.8 ns at adsorbed irradiance up to 1014 W cm-2. The effect of beam overlap on uniformity has been studied. © 1988.